Politics at the Time of Robots, Or: Is still there a “Principle of Hope”? - Montanari, Bruno (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
In a world dominated by information digital technologies, which determine an anthropological mutation, the basic question is: is still possible a critical theory of society? Indeed, the information digital technologies reduce the human reflective abilities to benefit from reactive abilities and, thus, they change the human sense of temporality: the a-temporality of reactivity takes the place of the diachronicity of reflection. We can find a possible answer in the categories of modern thought which, despite all tragical historical consequences, founded the rule of law. Keywords: digital technologies, critical theory, temporality, anthropological mutation.